Analysis of elasticity characteristics of ascending aorta, descending aorta and pulmonary artery using 640 slice-volume CT. Issue 26 (June 2018) - Yang, Fei; Wang, Dawei; Liu, Huaijun; Zhu, Xiaolong; Zou, Dianjun; Wang, Xiaocan; Hu, Zhenshun; Ji, Mengmeng; Cui, Shujun; Zhu, Yue xiang; Wen, Jing
Abstract : Abstract: As the prevalence of coronary computed tomographic angiography (CCTA), it is meaningful that CCTA can provide not only the structural details of artery, but also functional information of vessel elasticity. Our aim was to explore the elasticity characteristics of ascending aorta (AA), descending aorta (DA), main pulmonary artery (MPA), left pulmonary artery (LPA), right pulmonary artery (RPA), and their relationship between each other using 640 slice-volume computed tomography (CT). Furthermore, this study will also observe their relations with age. A total of 42 subjects that were free of cardiovascular disease, high blood pressure, diabetes, and hyperlipidemia underwent CCTA on 640 slice-volume CT and were enrolled in this study. The subjects were divided into 2 groups: Group 1, age <46; Group 2, age ≥46. The aortic distensibility (AD) and aortic compliance (AC) of aorta and pulmonary artery (PA) of each group were compared. The AD and AC of PA decreased in the following order: MPA, RPA, and LPA. The correlation coefficients of different elastic parameters between different vessels were found to be different. The correlation coefficient of AD between AA and DA, AA and MPA, DA and MPA, RPA and MPA, LPA and MPA, and RPA and LPA were 0.689 ( P = .000), 0.520 ( P = .000), 0.393 ( P = .010), 0.329 ( P = .033), 0.579 ( P = .000), and 0.534 ( P = .000), respectively. The correlation coefficients of AC for the 6 groups mentioned above were 0.351 ( P = .023), 0.470 ( P = .002), 0.249 ( P = .112), 0.190 ( P = .228), 0.441 ( P = .005), and 0.409 ( P = .010), respectively. There was an age-dependent decrease of AD and AC in AA, DA, MPA, LPA ( P < .05), but no difference in RPA ( P > .05). The elasticity characteristics of AA, DA, MPA, LPA, and RPA could be well shown by 640 slice-volume CT. The elasticity relativity was observed and was different between AA and DA, AA and MPA, LPA and MPA, LPA and RPA. An obvious age-related decrease in vascular elasticity was found in AA, DA, MPA, and LPA, which should be taken into consideration in clinical trials and treatments for the elasticity-related cardiovascular diseases.